2023
DOI: 10.9734/ijpss/2023/v35i213968
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sweet Corn and Increasing Soil Total Nitrogen after the Application of Vegetable Waste-Based Liquid Organic Fertilizer in Coastal Entisols

Zainal Muktamar,
Dicky P. Sinaga,
Heru Widiyono
et al.

Abstract: Coastal Entisols generally have coarse-textured, low organic matter and total soil nitrogen (N), and low water holding capacity. The liquid organic fertilizer is expected to increase soil organic matter in soil. The study's objective was to determine the total soil organic carbon (TSOC) and TSN on coastal Entisols and the performance of sweet corn under the application of liquid organic fertilizer (LOF) produced from vegetable waste. The study used a completely randomized design (CRD) with the treatments rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…This is consistent with the findings of Sun Yiming [33], who studied the variations in soil pH and SOM content under different land uses (dry fields, paddy fields, grasslands, forests, and unused land) over a period of 20 years and observed a sharp decrease in soil pH in northern China and a slight decrease in southern China over this period, with both regions experiencing a notable increase in SOM content. Zainal [34] indicated that applying liquid organic fertilizer to sweetcorn leads to a linear increase in the SOM and TN content, which is consistent with the findings of this study. Furthermore, the results of this study suggest that AP and AK are not the primary factors affecting daylily yield.…”
Section: Interactions Between Soil Physiochemical Properties and The ...supporting
confidence: 91%
“…This is consistent with the findings of Sun Yiming [33], who studied the variations in soil pH and SOM content under different land uses (dry fields, paddy fields, grasslands, forests, and unused land) over a period of 20 years and observed a sharp decrease in soil pH in northern China and a slight decrease in southern China over this period, with both regions experiencing a notable increase in SOM content. Zainal [34] indicated that applying liquid organic fertilizer to sweetcorn leads to a linear increase in the SOM and TN content, which is consistent with the findings of this study. Furthermore, the results of this study suggest that AP and AK are not the primary factors affecting daylily yield.…”
Section: Interactions Between Soil Physiochemical Properties and The ...supporting
confidence: 91%